Ginzburg-Landau theory for the magnetic and structural transitions in La 1-y (Ca 1-x Sr x ) y MnO 3 - León Hilario, L. M.; Aligia, Armando Ángel (IOP Publishing, 2019)
Fil: León Hilario, L. M.. Universidad Nacional de Ingenieria; Perú